Isolated right ventricular myocardial infarction misdiagnosed as anteroseptal myocardial infarction on ECG: a case report - Çağlar Özmen; Ali Deniz; Mehmet Kanadaşı (KARE Publishing, 2013)
In this article, we present a case with isolated right ventricular myocardial infarction (MI) who underwent coronary angiography on suspicion of acute anteroseptal MI detected on ECG; however, occlusion of the proximal right coronary artery (RCA) was detected. A female patient aged 65 years was brought to the emergency room due to loss of consciousness 1 hour before. From the patient's history, it was understood that she had undergone stent placement to her proximal RCA 5 days before. On ECG, a decreasing elevation in ST segment elevation from V1 to V4 was seen, and pathologic Q waves were present at DIII and AVF. A complete AV block was detected on ECG. In the coronary angiography, thrombosis of the stent in the proximal RCA was seen. Stenosis detected in the mid-left anterior descending artery was 50% and at the distal part was 60%. The circumflex coronary artery was found normal. Percutaneous transluminal coronary angioplasty was performed to the 95% thrombotic lesion in the stent of the proximal RCA, and full patency was established. In our case, a decreasing elevation in the ST segment elevation from V1 to V4 was seen. Right ventricular MI usually occurs by an acute stenosis of the non-dominant proximal RCA branch that does not receive collateral flow. In our case, RCA was codominant and an acute stenosis of the stent in the proximal RCA was present. The occlusion of the non-dominant RCA can appear as isolated right ventricular MI without causing a left ventricular infarct, since it does not feed the left ventricle.